Studying educational and social policy : theoretical concepts and research methods - Heck, Ronald H. (Sociocultural, political, and historical studies in education., 2004)
Ronald Heck seeks to introduce beginning researchers to the study of educational and social policy, how it has been examined from a scholarly perspective and the salient issues to consider in conceptualising and conducting policy research.